Analysis of covalent adaptable networks Based on disulfide exchange through broadband dielectric spectroscopy - B. Pascual-Jose; R. Teruel-Juanes; S. de la Flor; A. Serra; A. Ribes-Greus (Polymer Testing)
To study the nature and the cooperativity of the disulfide exchange mechanism in covalent adaptable networks, the dielectric and conductive properties of three membranes obtained by curing diglycidyl ether of bisphenol A (DGEBA) with hexamethylenediamine (HMDA), cystamine (CYS), or a mixture of both diamines in the same proportion were studied. Significant differences in the dielectric relaxation spectra of the three membranes were observed. In the low-temperature region, the dielectric spectra displayed two non-cooperative dielectric relaxations (γ and β). In the DGEBA/HMDA-CYS membrane, its relaxation function and activation energy are between those corresponding to the DGEBA/HDMA and DGEBA/CYS membranes, but their relationship does not depend linearly on the composition. In the high-temperature region, a dielectric relaxation of cooperative origin related to the glass transition (α) was observed in the membrane cured with hexamethylenediamine. However, the relaxation related to the glass transition overlaps with the exchange of the disulfide bonds in the membranes with cystamine. The analysis of the electric conductivity (σ) reveals an abrupt increment that suggests a radical-mediated dissociative bond exchange reaction may be occurring. However, the analysis of the σDC curves is indicative of an associative bond exchange reaction. The rapid formation of new associations among radicals is proposed to explain the vitrimer-like behaviour on these CYS-containing membranes.